The status and characteristics of urinary stone composition in China. (6th April 2020) - Ye, Zhangqun; Zeng, Guohua; Yang, Huan; Li, Jianxin; Tang, Kun; Wang, Guomin; Wang, Shusheng; Yu, Yonggang; Wang, Yujie; Zhang, Tao; Long, Yongfu; Li, Weibin; et al.
Abstract : Objectives: To explore characteristics of urinary stone composition in China, and determine the effects of gender, age, body mass index (BMI), stone location, and geographical region on stone composition. Patients and methods: We prospectively used Fourier‐transform infrared spectroscopy to analyse stones from consecutive patients presenting with new‐onset urolithiasis at 46 hospitals in seven geographical areas of China, between 1 June 2010 and 31 May 2015. Chi‐squared tests and logistic regression analyses were used to determine associations between stone composition and gender, age, BMI, stone location, and geographical region. Results: The most common stone constituents were: calcium oxalate (CaOx; 65.9%), carbapatite (15.6%), urate (12.4%), struvite (2.7%), and brushite (1.7%). CaOx and urate stones occurred more frequently in males, whereas carbapatite and struvite were more common in females ( P  < 0.01). CaOx and carbapatite were more common in those aged 30–50 and 20–40 years than in other groups. Brushite and struvite were most common amongst those aged <20 and >70 years. The detection rate of urate increased with age, whilst cystine decreased with age. Obese patients were more likely to have urate stones than carbapatite or brushite stones ( P  < 0.01). CaOx, carbapatite, brushite, and cystine stones were more frequently found in the kidney than other types, whereas urate and struvite were more frequent in the bladder ( P  < 0.01). Stone composition varied by geographical region. Conclusions: The most common stone composition was CaOx, followed by carbapatite, urate, struvite, and brushite. Stone composition differed significantly in patients grouped by gender, age, BMI, stone location, and geographical region.